IDENTIFIKASI SIFAT FISIOLOGIS DAN PRODUKSI TANAMAN JAMBU METE PADA KETINGGIAN TEMPAT BERBEDA DI KOTA BAUBAU, SULAWESI TENGGARA - Aliyaman Aliyaman; Asriyani Asriyani (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[IDENTIFICATION OF PHYSIOLOGICAL AND PRODUCTION PROPERTIES OF CASHEW AT DIFFERENT ALTITUDE IN BAUBAU CITY, SOUTHEAST SULAWESI]. Identification of physiological properties and production of cashew plants are very important to know as a reference for the community in managing cashew plants in Baubau City. The aim of this study was to identify the physiological properties and production of cashew at different altitudes in Baubau City Southeast Sulawesi Province. This research was conducted by survey method. The Samples observed were 10 plants that had productive age, which were about 20 years old per different altitude and came from farmers’ garden in Baubau City. The research was carried out through several stages namely the preparation stage, sampling, laboratory analysis and field observations. The plant variables observed were chlorophyll content, nitrate reductase activity, stomata density, stomata opening width, average production per tree, average production per hectare and weight of cashew nuts. The observational data were analyzed using analysis of variance with confidence level 5 % and if a significant difference was obtained between treatments, it was continued with Duncan’s Multiple Range Test. The result showed that the difference in altitude significantly affected the physiological properties and production of cashew in Baubau City. Physiologically, the research location with an altitude of 0-500 masl has higher chlorophyll content, nitrat reductase activity and stomata density than cashew platnts at locations >1000 masl. While in terms of crop production, the research location with an altitude of 500-1000 masl has a higher average production per hectare than cashew plants at locations 0-500 masl and >1000 masl.